2019
DOI: 10.1037/apl0000341
|View full text |Cite
|
Sign up to set email alerts
|

Leaders matter morally: The role of ethical leadership in shaping employee moral cognition and misconduct.

Abstract: There has long been interest in how leaders influence the unethical behavior of those who they lead. However, research in this area has tended to focus on leaders' direct influence over subordinate behavior, such as through role modeling or eliciting positive social exchange. We extend this research by examining how ethical leaders affect how employees construe morally problematic decisions, ultimately influencing their behavior. Across four studies, diverse in methods (lab and field) and national context (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 103 publications
(162 reference statements)
11
150
2
2
Order By: Relevance
“…Specifically, the village cadres could put effort into formulating a village public health governance scheme with the effective participation of the villagers. Then, the villagers can master this scheme in various ways, which could help them to internalize the epidemic prevention and control rules into their moral obligation [53]. On the other hand, village cadres' public leadership, as an external constraint for villagers, can effectively motivate villagers to participate in collective action for epidemic prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the village cadres could put effort into formulating a village public health governance scheme with the effective participation of the villagers. Then, the villagers can master this scheme in various ways, which could help them to internalize the epidemic prevention and control rules into their moral obligation [53]. On the other hand, village cadres' public leadership, as an external constraint for villagers, can effectively motivate villagers to participate in collective action for epidemic prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Hodge and Lonsdale found that moral disengagement mediated the relationship between controlling coaching styles and higher levels of anti-social behavior toward teammates and opponents [24]. Moore et al have similarly found that moral disengagement mediates the relationship between how ethical an employee's leader is and the likelihood they will engage in unethical workplace behavior [53]. Moral disengagement has also been studied as a mediator in the relationship between positive ethical antecedents and outcomes.…”
Section: Moral Disengagement As a Mediatormentioning
confidence: 99%
“…In their study of youth offenders, DeLisi et al found that the relationship between psychopathy and criminal behavior was direct for delinquents who showed high levels of psychopathy, but was mediated through moral disengagement for youths who had lower levels of psychopathy [20 ]. Relatedly, Moore et al found that the indirect relationship between ethical leaders and employee misconduct through moral disengagement was moderated by employees' moral identities: whether ethical leaders inspired more ethical behavior or unethical leaders encouraged more deviant behavior through moral disengagement depended on how important being moral was to the employee in the first place [53]. These studies hint at the complex interactive processes that combine to produce our moral behavior: a function of who we are when we enter a given context, as well as how that context affects us.…”
Section: Moral Disengagement As a Mediatormentioning
confidence: 99%
“…Scholars have also examined why leaders who behave ethically promote the ethical behaviour of their followers. Two theories to describe this transmission process are social learning theory and social exchange theory (Brown & Treviño, ; Brown et al, ; Moore et al, ). Social learning theory (Bandura, ) establishes that virtually anything can be learned through vicarious learning, enacted through a person who acts as a role model and uses rewards and punishments.…”
Section: Introductionmentioning
confidence: 99%